Von dynamischen Grenzen und unsichtbaren Machtachsen: Intersektionale Theoriebildung und ihre Impulse für eine theologische Sozialethik angesichts algorithmischer Klassifizierung - Ott, Tabea (Solidarität. Intersektionale Dimensionen feministisch-theologischer Ethik, 2025)
Intersectionality has become a buzzword in the humanities, yet it often remains ill-defined or is used inconsistently depending on the subject area. On the one hand, intersectionality still needs refinement and lacks scientific acknowledgement. Particularly in German-speaking theological ethics, intersectionality has been little discussed. On the other hand, intersectionality seems to be so established, especially in the Anglo-American context, that the intersection of gender and race is far from questioned anymore. However, both stances overlook the inherent dimensions of intersectionality, failing to effectively tackle the challenges posed by algorithmic classification. These challenges stem from the ongoing creation of new intersections and the superimposition or obscuration of existing ones. However, intersectionality understood as a knowledge project promises to address the challenges effectively. Therefore, the paper identifies key dimensions of what constitutes intersectionality. First, intersectional theories aim to de-marginalize the intersection where discrimination and injustice occur. Second, intersectional theories identify the intersections as multiple, non-hierarchical, and dynamic entanglements. Third, intersectional theories are often misunderstood as identity politics. However, they function as a critique of power and the pursuit of justice. From these three dimensions of intersectional theories, the paper draws socio-ethical implications for algorithmic classification. The in-depth analysis shows that intersectional theory is able to expose the difficulties of using categories and classifiers as well as aggregating and disaggregating data in the context of Artificial Intelligence. The paper points out that the disaggregation of data and fine-grained analysis can only take place where political protection mechanisms ensure that individuals and groups are not harme